Broiler responses to dietary 3,4,5-trihydroxybenzoic acid and oregano extracts under Eimeria challenge conditions - Yu, Myunghwan; Jeon, Jong Oh; Cho, Hyun Min; Hong, Jun Seon; Kim, Yu Bin; Nawarathne, Shan Randima; Wickramasuriya, Samiru Sudharaka; Yi, Young-Joo; Lee, Hans; Wan, Vannie; Ng, Noele Kai Jing; Tan, Chuan Hao; et al. (Journal of animal science and technology, 2021)
This study was conducted to evaluate the efficacy of a combination 3,4,5-trihydroxybenzoic acid (THB) and oregano extracts (i.e., Carvacrol and Thymol) at intake/dietary different levels on growth performance, intestinal health indicators, immune responses and fecal oocyst shedding in broiler chickens under challenged condition. A total of 336 one-day-old broilers were randomly assigned to one of six dietary treatments with seven replications per treatment. Dietary treatments were: i) Non-challenged bird without any dietary treatment (NCNT), ii) Challenged bird without any dietary treatment (CNT), iii) Challenged birds fed a THB diet (0.1 g/kg, THB), iv) Challenged birds fed a combination of THB and oregano extracts diet (0.1 g/kg, COM 100), and a gradual increase of combination of THB and oregano extracts likely v) 0.15 g/kg (COM 150), and 0.2 g/kg (COM 200). On day 14, all groups except for NCNT have orally challenged with a 10-fold dose of Livacox® T anticoccidial vaccine to trigger coccidiosis. The results indicated that -challenged broilers fed COM 100 and COM 200 diets increased ( < 0.05) body weight than CNT diet on day 35. Furthermore, birds fed COM 100 and COM 200 diets increased ( < 0.05) average daily gain compared to those fed CNT diets for the entire experimental period. There is no significant ( > 0.05) in average daily feed intake, feed efficiency between NCNT and birds fed with combined THB and oregano extracts for the entire experimental period. A combination of THB and oregano extract regardless of concentration levels or THB alone reduced ( < 0.05) lesion score in ileum compared to the CNT diet for 7 days post-infection (dpi). Birds fed COM 100 diet had lower ( < 0.05) intestinal lesion scores in jejunum and caeca on 7 dpi compared to those were in the CNT diet. No ( > 0.05) difference was observed in the oocysts per gram of feces count, intestinal morphology, carcass traits and blood cytokine concentration among the infected treatments. Collectively, we conclude that birds fed with a combination of THB and oregano extracts regardless of the ratios that were used demonstrated better recovery of health after the coccidial challenge than using only THB alone.